Unicidade de estados de equilíbrio para ferraduras parcialmente hiperbólicas - Oliveira, Marlon Cesar Santos (2017)
In this work we show the uniqueness of equilibrium state for a family of partially hyperbolic horseshoes introduced by [9] associated to a class of hyperbolic Hölder continous potentials. The method used here is to build a symbolic system with infinitely many symbols, show that the induced potential is Hölder and recurrent and make use of Sarig’s theory for countable shifts. Moreover, we prove the uniqueness of maximal entropy measures for a class of horseshoes intruduced by [8].